ROLE OF CREDIBLE INTELLIGENCE IN ENHANCING INTERNAL SECURITY OPERATIONS IN NIGERIA: A CRITICAL ANALYSIS - Ibekwe, Emmanuel Ogueri (African Journal of Social and Behavioural Sciences, 2025)
This study examines how credible intelligence contributes to improving internal security operations in Nigeria. Despite the presence of several security agencies, such as the Department of State Services (DSS), Force Intelligence Department (FID), Directorate of Military Intelligence (DMI), Directorate of Naval Intelligence (DNI), Air Intelligence Division (AID), Directorate of Intelligence and Investigation (DII) and the Defence Intelligence Agency (DIA), Nigeria continues to experience serious security threats, including terrorism, insurgency, banditry, and kidnapping. The research highlights how timely, accurate, and reliable intelligence can help prevent attacks, guide security operations, and improve coordination among agencies. It explores the main types of intelligence used – Human Intelligence (HUMINT), Signals Intelligence (SIGINT), and Open Source Intelligence (OSINT) – and how they support decision-making in security matters. The study also identifies key challenges facing intelligence operations, such as poor inter-agency collaboration, lack of modern technology, limited funding, and low community trust. Through real-life examples and case studies, the study examined the benefits of intelligence led security efforts and the risks of faulty intelligence. The study concludes with recommendations to improve intelligence gathering and use, including creating a central coordination agency, involving communities more effectively, investing in technology, and strengthening international partnerships. These steps are necessary to build a safer and more secure Nigeria.